Telitacicept Following Plasma Exchange in the Treatment of Subjects With Recurrent NMOSD: Study Protocol for a Single-Center, Single-Arm, Open-Label Study - Ding, Jie; Cai, Yu; Deng, Ye; Jiang, Xianguo; Gao, Meichun; Lin, Yan; Zhao, Nan; Wang, Ze; Yu, Haojun; Lv, Wenwen; Zhang, Ying; Hao, Yong; et al. (Frontiers in neurology, 2021)
Background: Neuromyelitis optica spectrum disorder (NMOSD) is an autoimmune demyelinating disease that recurrently relapses and leads to severe disability. The available choices for disease prevention are few or intolerable. Previous studies suggested that telitacicept may provide a promising therapeutic strategy for autoimmune diseases involving B cells. Therefore, this study aims to assess the effectiveness and safety of telitacicept for recurrent NMOSD. Methods: We will perform a single-arm, single-center, open-label, specialist study with a total enrollment of eight participants. The treatment regimen includes plasma exchange three times and subcutaneous injection of telitacicept for 46 cycles, with a total period of 48 weeks. The primary endpoint is the time to first recurrence after enrollment. Secondary endpoints are Expanded Disability Status Scale (EDSS) score, Opticospinal Impairment Scale (OSIS) score, Hauser Ambulation Index, number of lesions on MRI, and changes in visual evoked potential (VEP), optical coherence tomography (OCT) and immunologic status. All adverse events after medication will be documented and investigated. Discussion: This study will explore the safety and effectiveness of telitacicept following plasma exchange regarding the time to recurrence in neuromyelitis optica spectrum disorder (NMOSD) for the first time. Clinical Trial Registration: Chictr.org.cn , identifier ChiCTR1800019427